Analysis of the Literature on the Role of Physical Activity in Improving Wellbeing and Quality of Life - Nur, Rezeki; Erliana, Yossy Dwi; Tjahyadi, Indra; Mardikawati , Budi (West Science Interdisciplinary Studies, 2023)
This study undertakes a thorough bibliometric analysis to investigate how the body of research on the benefits of physical activity for improving wellbeing and quality of life is changing. The study examines authorship patterns, citation networks, theme clusters, and keyword co-occurrences using data from well-known databases in order to offer a comprehensive picture of the area. Important writers including DER Warburton, CE Garber, and WL Haskell have produced seminal works that serve as a basis for international principles and recommendations. The impact of physical activity on overall health to the impact of adolescent and mental health are just a few of the varied dimensions covered by thematic clusters in the research. Recurring themes are found by keyword co-occurrence analysis, one of which being the general impact of physical activity on life and quality. Unexplored topics, such how exercise affects diseases like multiple sclerosis and the COVID-19 pandemic's effects, indicate areas that warrant more study. The amalgamation of results provides significant perspectives for scholars, professionals, and decision-makers seeking to propel understanding and guide evidence-based solutions concerning physical activity and wellness.